Reputation: 1505
Let's say I have two different functions that reverse a list:
revDumb : List a -> List a
revDumb [] = []
revDumb (x :: xs) = revDumb xs ++ [x]
revOnto : List a -> List a -> List a
revOnto acc [] = acc
revOnto acc (x :: xs) = revOnto (x :: acc) xs
revAcc : List a -> List a
revAcc = revOnto []
and now I want to prove that these functions indeed do the same thing. This is the proof that I came up with:
mutual
lemma1 : (acc, lst : List a) -> revOnto acc lst = revOnto [] lst ++ acc
lemma1 acc [] = Refl
lemma1 lst (y :: ys) = let rec1 = lemma1 (y :: lst) ys
rec2 = lemma2 y ys in
rewrite rec1 in
rewrite rec2 in
rewrite appendAssociative (revOnto [] ys) [y] lst in Refl
lemma2 : (x0 : a) -> (xs : List a) -> revOnto [x0] xs = revOnto [] xs ++ [x0]
lemma2 x0 [] = Refl
lemma2 x0 (x :: xs) = let rec1 = lemma2 x xs
rec2 = lemma1 [x, x0] xs in
rewrite rec1 in
rewrite sym $ appendAssociative (revOnto [] xs) [x] [x0] in rec2
revsEq : (xs : List a) -> revAcc xs = revDumb xs
revsEq [] = Refl
revsEq (x :: xs) = let rec = revsEq xs in
rewrite sym rec in lemma2 x xs
This even type checks and is total (despite the mutual recursion):
*Reverse> :total revsEq
Reverse.revsEq is Total
Note that lemma1
is effectively a stronger version of the lemma2
, yet I seemingly need lemma2
since it simplifies the recursive case in lemma1
.
The question is: can I do any better? Mutually recursive lemmas with lots of rewrites seem to be overly opaque.
Upvotes: 1
Views: 321
Reputation: 3722
If you do the recursion on a function that keeps revOnto
's accumulator explicit, the proof can be quite short:
lemma1 : (acc, xs : List a) -> revOnto acc xs = revDumb xs ++ acc
lemma1 acc [] = Refl
lemma1 acc (y :: xs) =
rewrite lemma1 (y :: acc) xs in
appendAssociative (revDumb xs) [y] acc
revsEq : (xs : List a) -> revAcc xs = revDumb xs
revsEq [] = Refl
revsEq (x :: xs) = lemma1 [x] xs
Upvotes: 1